TIJORAT BANKLARIDA MOLIYAVIY JINOYATLARNING OLDINI OLISHDA KOMPLAYENS-NAZORATNING ROLI (Marketing Journal, 2026)
AbstractThe article analyzed the role of the compliance control system in preventingfinancial crimes in commercial banks. The study examined internal controlmechanisms, monitoring processes based on AML/CFT requirements, and theimplementation of a risk-based approach. The institutional status of compliance units,their level of independence, and integration with digital technologies were assessed.The effectiveness of KYC procedures and automated analytical tools in detectingsuspicious transactions was demonstrated. The findings confirmed that strengtheningthe compliance function at the strategic level contributes to reducing financial risks.Based on the results, practical recommendations for improving the system weredeveloped. Keywords: compliance control, financial crimes, banking system, AML/CFT,internal control